Polymorphism of the 5′ flanking region of the IL-12 receptor β2 gene partially determines the clinical types of leprosy through impaired transcriptional activity. Issue 7 (23rd June 2005) - Ohyama, H; Ogata, K; Takeuchi, K; Namisato, M; Fukutomi, Y; Nishimura, F; Naruishi, H; Ohira, T; Hashimoto, K; Liu, T; Suzuki, M; Uemura, Y; et al.
Abstract : Background: Individual differences in T cell responsiveness to interleukin 12 (IL-12), resulting from inherited factors, may be responsible for differences in the intensity of cell mediated immune (CMI) responses in patients with leprosy, a disease with a wide clinical spectrum. Aim: Polymorphisms in the 5′ flanking region of the IL12RB2 gene were analysed to determine potential immunogenetic factors affecting CMI responses, using leprosy as a model. Methods: Polymorphisms in the 5′ flanking region of IL12RB2 were examined using direct sequencing techniques, and allele frequencies between patients with lepromatous leprosy and patients with tuberculoid leprosy were compared. The effect of these single nucleotide polymorphisms (SNPs) on IL12RB2 expression was estimated using the dual luciferase reporter gene assay in Jurkat T cells. Results: Several SNPs, including −1035A>G, −1023A>G, −650delG, and −465A>G, were detected within the 5′ flanking region of IL12RB2. The frequency of haplotype 1 (−1035A, −1023A, −650G, −464A) was high in the general Japanese population, but was significantly lower in lepromatous patients compared with tuberculoid patients and healthy controls. Reporter gene assays using Jurkat T cells revealed that all haplotypes carrying one or more SNP exhibited a lower transcriptional activity compared with haplotype 1. Conclusion: SNPs within the 5′ flanking region of IL12RB2 affect the degree of expression of this gene and may be implicated in individual differences in CMI responsiveness to mycobacterial antigens, leading to lepromatous or tuberculoid leprosy.